Inverse kinematics of a serial-parallel robot used in hot forging process - My, Chu Anh (Vietnam Journal of Mechanics, 2016)
In hot extrusion forging process, the use of  robot arm for transferring heavy billets can reduce downtime, improve  productivity, reduce worker fatigue and optimize the use of~energy and  manpower. To increase the stiffness of the robot and force the end-effector  move in directions parallel with the ground surface, two parallel links are  added to a standard serial manipulator. This modification of the structure  could make it a bit of challenge in the system modelling and controlling.  This paper addresses the inverse kinematics analysis that is the central  issue for developing autonomous control modes of the robot application.